2012
DOI: 10.1111/j.1365-246x.2012.05613.x
|View full text |Cite
|
Sign up to set email alerts
|

A shear wave velocity model of the European upper mantle from automated inversion of seismic shear and surface waveforms

Abstract: SUMMARY We present a new, S‐velocity model of the European upper mantle, constrained by inversions of seismic waveforms from broad‐band stations in Europe and surrounding regions. We collected seismograms for the years 1990–2007 from all permanent stations in Europe for which data were available. In addition, we incorporated data from temporary experiments. Automated multimode inversion of surface and S‐wave forms was applied to extract structural information from the seismograms, in the form of linear equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
89
4
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 172 publications
14
89
4
1
Order By: Relevance
“…The higher velocity values in this area are observed down to about 200 km, which coincides well with the studies by WildePiórko et al (2010), Majorowicz et al (2003) and Koulakov et al (2009). Legendre et al (2012) found the highest velocity values in the mantle of the EEC at about 150 km depth. Further to the northeast of the TESZ, the high-velocity area goes deeper, and beneath the territory of Lithuania, we find the thickest lithosphere of about 300 km or more (Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The higher velocity values in this area are observed down to about 200 km, which coincides well with the studies by WildePiórko et al (2010), Majorowicz et al (2003) and Koulakov et al (2009). Legendre et al (2012) found the highest velocity values in the mantle of the EEC at about 150 km depth. Further to the northeast of the TESZ, the high-velocity area goes deeper, and beneath the territory of Lithuania, we find the thickest lithosphere of about 300 km or more (Fig.…”
Section: Resultssupporting
confidence: 80%
“…Koulakov et al (2009) observed the positive P wave velocity anomaly beneath the EEC down to at least 300 km, which indicates even thicker lithosphere compared to . Legendre et al (2012) find no indications of a deep cratonic root below about 330 km for the EEC, while Geissler et al (2010) do not observe any clear indications of deep seismic LAB beneath the EEC either.…”
Section: Review Of Previous Studiesmentioning
confidence: 75%
“…Meier et al (2007) identified two slab segments and proposed that they are associated with laterally varying properties of the African slab. Furthermore, in the Mediterranean southeast of Crete, Rhodes and south of western Anatolia, high velocities in the mantle lithosphere -typical for cold oceanic lithosphere -are found by tomographic studies (Bijward et al, 1998;Marone et al, 2004;Endrun et al, 2008;Legendre et al, 2012), whereas south of Peloponnese and western Crete velocities in the mantle lithosphere are lower Legendre et al, 2012).…”
Section: F Sodoudi Et Al: Receiver Function Images Of the Hellenic mentioning
confidence: 99%
“…More recently, Koulakov et al (2009) have constructed P and S tomography models for the upper mantle beneath Europe, which took into account a newly obtained crustal model by Tesauro et al (2008). In parallel there were several models of Europe created based on surface-wave data (Boschi et al, 2004(Boschi et al, , 2009Marone et al, 2004;Legendre et al, 2012). Adjoint tomography has been used for studying the European region by Zhu et al (2012).…”
Section: Introductionmentioning
confidence: 99%